2018
DOI: 10.1111/tri.13306
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion settings and additives in liver normothermic machine perfusion with red blood cells as oxygen carrier. A systematic review of human and porcine perfusion protocols

Abstract: Liver machine perfusion (MP) at normothermic temperature (NMP) is a promising way to preserve and evaluate extended criteria donor livers. Currently, no consensus exists in methodology and perfusion protocols. Here, the authors performed a systematic literature search to identify human and porcine studies reporting on liver NMP with red blood cells. A qualitative synthesis was performed concerning technical aspects of MP, fluid composition, gas supply, and liver positioning. Thirty-seven publications including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 84 publications
0
44
0
Order By: Relevance
“…Moreover, the analysis of the perfusate may help to evaluate organ viability even in hypothermic conditions, and the infusion of therapeutic agents -e.g. nutrition, mesenchymal stromal cells (MSC) and extracellular vesicles releasing by MSC, anti-inflammatory and anti-apoptotic additives -might be a simple implement of the perfusion system in use [42][43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the analysis of the perfusate may help to evaluate organ viability even in hypothermic conditions, and the infusion of therapeutic agents -e.g. nutrition, mesenchymal stromal cells (MSC) and extracellular vesicles releasing by MSC, anti-inflammatory and anti-apoptotic additives -might be a simple implement of the perfusion system in use [42][43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…We first perfused pig livers with a hyperglycemic perfusate (perfusate glucose >10 mmol l −1 ) at fixed insulin injection rates (0.9 U h −1 ). Although glucose is not the primary energy source for hepatocytes 10 , perfusion protocols available in the literature 4,5,11,12 have used this approach. For example, the pioneering randomized controlled trial of normothermic liver perfusion in humans also reported high glucose levels in the perfusate (>10 mmol l −1 ) at a constant insulin injection rate (7 U h −1 ) 5 .…”
mentioning
confidence: 99%
“…
Dear Editors, With interest, we have read the systematic review by Eshmuminov et al regarding porcine and human liver normothermic machine perfusion (NMP) [1]. The authors focused on studies using red blood cells (RBC) as oxygen carrier in the perfusion fluid and excluded studies using perfusion solutions based on artificial oxygen carriers.
…”
mentioning
confidence: 99%